TUNA FISH HEAD OIL (Thunnus sp)PURIFICATION USING BENTONIT - Saputra, Tri Wahyudi; Ilza, Mirna; Edison, Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACK This            The study aims to determine the effect of the bentonite adsorbent added when refining fish oil. The method used in this research is the experimental method. The design used was a non-factorial Completely Randomized Design (CRD). The bentonite concentration treatment factors used M1 (7%), M2 (10%) and M3 (13%). The test parameters used were proximate analysis (free fatty acid content, peroxide number and moisture content) and organoleptic test (color and aroma). The results showed that the addition of bentonite with different concentrations to the quality of tuna fish head oil had a significant effect on the value of color and aroma at the 95% confidence level with the best organoleptic quality found in the M3 treatment with a characteristic golden yellow color (8.39) and more aroma fish oil specifics (8.33). The results of chemical analysis of tuna fish head oil purification (Thunuus sp) using bentonite are peroxide number 2.32meq/kg, free fatty acids 1.38% and moisture content of 2.29%.Keywords: Fish oil, bentonite, peroxide number